Comparison of free radicals and antioxidant enzymes in chronic otitis media with and without tympanosclerosis - Karlidag, T; Ilhan, N; Kaygusuz, I; Keles, E; Yalçin, S (Wiley, 2004)
Objective/Hypothesis: The pathogenesis of tympanosclerosis is unclear. The study was performed to investigate the role of nitric oxide, free oxygen radicals, and antioxidants in development of tympanosclerosis in patients with chronic otitis media. Study Design: A prospective study in patients with nasal polyps. Methods: Sixty-five patients who underwent tympanoplasty or tympanoplasty together with mastoidectomy were included in the study. Preoperative venous blood samples were drawn, and serum sodium, potassium, calcium, alkaline phosphatase, inorganic phosphorus, parathormone, and calcitonin levels were measured. The patients who had tympanosclerotic plaques on tympanic membrane or middle ear mucosa or near the ossicular chain or mastoid bone were designated as group 1 (n = 34), and the remaining patients as group 2 (n = 31). Intraoperatively, specimens were obtained from the middle ear mucosa and tympanic membrane to measure nitric oxide and malondialdehyde levels. In addition, plasma malondialdehyde levels and erythrocyte superoxide dismutase and catalase activity were determined. Results: All patients had similar demographic features and serum electrolyte and hormone levels. Nitric oxide and malondialdehyde levels of the specimens obtained from the middle ear mucosa (P =.001) and tympanic membrane (P =.01) and, in parallel to this, the plasma malondialdehyde activity level were higher in group 1 than in group 2. Moreover, group 2 had significantly lower erythrocyte catalase activity levels (P =.001) compared with group 1, whereas such a significant difference was not present for superoxide dismutase activity levels (P >.05). Conclusion: The study results suggest that nitric oxide, free oxygen radicals, and catalase may have a role in the development of tympanosclerosis in patients with chronic otitis media.
Keywords: Tympanosclerosis; nitric oxide; free oxygen radicals; antioxidant